When digital engagement becomes dysregulated: associations with aggression, achievement motivation, and academic performance in adolescents - Minghua Dong; Huitao He; Bowen Wei (Frontiers in Public Health, 2026)
Introduction Adolescents are embedded in digital environments that are increasingly central to social, academic, and emotional life. Yet the developmental implications of digital engagement remain contested, particularly when exposure metrics such as screen time are used as primary indicators. The present study examined digital engagement as a multidimensional construct while treating regulatory difficulty—the dimension most directly reflecting impaired control and difficulty disengaging—as the focal predictor of aggression, achievement motivation, and objectively measured academic performance. Methods Participants were 309 secondary school students in eastern China (Mage = 14.52 years) who completed self-report measures of dysregulated digital engagement, multidimensional aggression, and achievement motivation; official semester GPA was obtained from school records. Confirmatory factor analyses were conducted to evaluate the measurement structure of the scales. Correlational analyses and classroom-cluster-adjusted hierarchical modeling were used to examine associations between regulatory difficulty and the study outcomes while accounting for demographic and design-related covariates, total aggression, and achievement motivation. Results Confirmatory factor analyses supported the measurement structure of all scales. Correlational analyses indicated that dysregulated engagement was positively associated with aggression and negatively associated with achievement motivation and GPA. In the classroom-cluster-adjusted hierarchical model, regulatory difficulty showed a modest incremental negative association with GPA after demographic and design-related covariates, total aggression, and achievement motivation were statistically accounted for. Discussion Findings are consistent with a self-regulation perspective and indicate that dysregulated characteristics of digital engagement are meaningfully associated with adolescent academic functioning. Because digital exposure duration was not independently assessed, the present findings should be interpreted as complementing, rather than directly contrasting with, screen-time research. These findings highlight the potential value of focusing on digital self-regulation, rather than exposure duration alone, in future research and educational practice.